2011
DOI: 10.4314/sajas.v41i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed on milk fatty acid profile in dairy ewes, with particular reference to <i>cis-9, trans-11</i> conjugated linoleic acid

Abstract: ________________________________________________________________________________ AbstractThe objective of this study was to determine and compare the fatty acid profile of milk fat, with particular reference to cis-9, trans-11 conjugated linoleic acid (CLA), in two indigenous Romanian sheep breeds (Spanca and Turcana), irrespective of the effects of diet and season. The ewes (n = 25 for each breed) received the same feed (total mixed rations) and were maintained under identical conditions. Four samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 29 publications
(56 reference statements)
3
29
1
11
Order By: Relevance
“…standard error of mean, SFA saturated fatty acids, TI thrombogenic index, UFA unsaturated fatty acids, UFA/SFA unsaturated fatty acids/ saturated fatty acids, ω-6/ω-3 omega-6 fatty acids/omega-3 fatty acids ) in the same row represent significant differences between breeds with P<0.05 in *, with P<0.01 in ** and with P<0.001 in *** atherogenic index (AI) showed significantly (P < 0.05) higher values than the thrombogenic index (TI) in raw milk and cream fat (Tables 2 and 4). Therefore, atherogenic index values of sheep raw milk fat were found to be almost half of those reported by Nantapo et al (2014) for cow milk fat, similar to those reported by Soják et al (2013) for ewe milk fat and lower to those reported by Mierlita et al (2011) for Spanca ewe milk fat. The most interesting features in raw milk and cream fat, according to the above data, were the high proportions of short-and medium-chain fatty acids (SCFA and MCFA), as well as the existence of CLA isomers and PUFA even at low proportions.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…standard error of mean, SFA saturated fatty acids, TI thrombogenic index, UFA unsaturated fatty acids, UFA/SFA unsaturated fatty acids/ saturated fatty acids, ω-6/ω-3 omega-6 fatty acids/omega-3 fatty acids ) in the same row represent significant differences between breeds with P<0.05 in *, with P<0.01 in ** and with P<0.001 in *** atherogenic index (AI) showed significantly (P < 0.05) higher values than the thrombogenic index (TI) in raw milk and cream fat (Tables 2 and 4). Therefore, atherogenic index values of sheep raw milk fat were found to be almost half of those reported by Nantapo et al (2014) for cow milk fat, similar to those reported by Soják et al (2013) for ewe milk fat and lower to those reported by Mierlita et al (2011) for Spanca ewe milk fat. The most interesting features in raw milk and cream fat, according to the above data, were the high proportions of short-and medium-chain fatty acids (SCFA and MCFA), as well as the existence of CLA isomers and PUFA even at low proportions.…”
Section: Discussionsupporting
confidence: 64%
“…In accordance with Signorelli et al's (2008) findings, FA profile could be proposed as an indicator of breed type. In the same sense, Mierlita et al (2011) reported that breed markedly affects the FA profile of ewe milk fat.…”
Section: Effect Of Breed On Fatty Acid Profile and Lqi Of Raw Milk Anmentioning
confidence: 85%
See 1 more Smart Citation
“…Tsiplakou et al (2006) and Signorelli et al (2008) did not find any significant effect of the breed on CLA in milk from different breeds of sheep maintained under the same feeding regimes, but this was due to the large variation in milk fat CLA content among individuals. When comparing the fatty-acid profile of milk from indigenous Romanian sheep breeds (Spanca and Turcana), Mierlita et al (2011) found differences for the majority of FA. The Turcana breed was characterized by lower SFA, and higher MUFA and PUFA contents.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed in the CLA content are very important because in the last years CLA has aroused much attention due to its anticarcinogenic activity, antiatherogenic, anti-obesity, anti-diabetes, and immune-stimulating properties (Crumb & Vattem 2011). Previous studies were focused mainly on the effect of sheep breed on the milk fatty acid profile (Signorelli et al 2008;Talpur et al 2009;Mierlita et al 2011), whereas the effect of breed on cheese quality was investigated to a lesser extent. Secchiari et al (2001) observed the breed effect (2014) is one of the few studies carried out simultaneously on milk and cheese made from different sheep breeds in Poland; they observed the breed effect on some isomers of CLA (CLA c9,t11;CLA t10,c12,and CLA c9,c11) in "oscypek" cheese manufactured from milk of different Polish breeds.…”
Section: Food Technology and Economy Engineering And Physical Propermentioning
confidence: 99%